ANALISIS EFEKTIVITAS PEMBIASAAN SHOLAT DHUHA TERHADAP PENANAMAN KARAKTER AKHLAK MULIA SISWA SDIT PERSIS 99 RANCABANGO - Rahma Novianti; Muhammad Nurjamaludin; Delia Sri Agustiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The practice of performing the Dhuha prayer is one effort to instill noble moral character in elementary school students. This study aims to analyze the effectiveness of habituating the Dhuha prayer in fostering noble moral character among students of SDIT Persis 99 Rancabango. Through activities carried out routinely, students are accustomed to being disciplined, responsible, and developing religious values in their daily lives. Thus, the habituation of the Dhuha prayer becomes an effective strategy in supporting the cultivation of noble moral character in line with the school culture.